D:A friedo-oleanane lactones from the stems of Mallotus repandus - Somyote Sutthivaiyakit (2018)
Three new D:A-friedo-oleanane lactones, viz., 3-oxo-D:A-friedo-oleanan-27,16α-lactone (1), 3α-benzoyloxy-D:A-friedo-oleanan-27,16α-lactone (2), and 3β-hydroxy-D:A-friedo-oleanan-27,16α-lactone (3) were isolated from the stems of Mallotus repandus. Extensive use of NMR spectroscopic techniques led to full assignment of all 1H and 13C chemical shifts. The structure for 2 was confirmed by X-ray diffraction analysis.